A fluorinated polymer sponge with superhydrophobicity for high-performance biomechanical energy harvesting. (July 2021) - Peng, Zehua; Song, Jian; Gao, Yuan; Liu, Jin; Lee, Ching; Chen, Guorui; Wang, Zuankai; Chen, Jun; Leung, Michael K.H.
Abstract: Human body contains various biomechanical energy, which emerges as a pervasive and sustainable energy resource for wearable electronics in the era of Internet of Things. We have developed a fluorinated polymer sponge based triboelectric nanogenerator (FPS-TENG) that provides stable electrical output over a wide range of ambient humidity. The humidity resistance due to excellent hydrophobic property of the fluorinated polymer sponge can overcome the adverse effects of moisture. The FPS-TENG also exhibits high durability even after enduring heavy abrasion. The output voltage of the FPS-TENG is three times higher than that of the pristine polymer film (PPF) based TENG. When assembled with hydrophobic copper (HC) contact electrodes, the FPS-TENG retains almost 90% electrical output over 20–85% relative humidity. Moreover, super durability is achieved by quasi-bulk-phase functionalization. After 1 mm-thickness abrasion of the fluorinated polymer sponge, the output voltage is degraded by only 10%. Under the optimal operating conditions, the FPS-TENG delivers a maximum power density of 0.89 W m −2 at a load resistance of 10 MΩ. The fluorination enhanced triboelectrification and the surface superhydrophobicity induced humidity-stability make the FPS-TENG a sustainable power source for the wearable bioelectronics in the era of Internet of Things. Graphical Abstract: ga1 Highlights: Moisture-resistant triboelectric nanogenerator was developed. Fluorination treatment effectively improves hydrophobicity. Quasi-bulk-phase functionalization enables super durability. Parametric experimental results yield optimal material design.